High-wettability aramid fiber coated diaphragm and preparation method thereof

By adopting high-impact aramid coating technology on the lithium-ion battery separator, the problem of poor wetting of the electrolyte of the non-woven separator is solved, high-impactivity and stable electrochemical performance are achieved, and the performance requirements of high-end products are met.

CN119651055APending Publication Date: 2025-03-18TAIZHOU JICUI FENGFANG NEW MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411968999.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Non-woven separators have the problem of poor electrolyte wetting in lithium-ion batteries, which is difficult to meet the performance requirements of high-end products for lithium batteries.

Method used

The separator is coated with a high wettability aramid. By coating the aramid slurry on the base film, the base film with a composite structure and the coating with a porous structure is formed, and the porous structure of the non-woven fabric layer and the fibrillated fiber layer are optimized to improve the compatibility and wettability of the electrolyte.

Benefits of technology

It achieves high wetting and stable electrochemical properties, overcomes the problems of insufficient thermal stability and wetting properties of non-woven separators, and meets the requirements of high-temperature dimensional stability and heat resistance of lithium-ion batteries for high-end products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219068240000071
    Figure BDA0005219068240000071
  • Figure BDA0005219068240000081
    Figure BDA0005219068240000081
  • Figure BDA0005219068240000091
    Figure BDA0005219068240000091
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery components, and particularly discloses a high-wettability aramid fiber coated diaphragm and a preparation method thereof. According to the application, the non-woven fabric layer and the fibrillated fiber layer are assembled to obtain the base membrane with a composite structure, and the coating is formed on the surface of the base membrane by using the aramid fiber slurry. Under the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating, the high-wettability aramid fiber coated diaphragm can fully infiltrate and absorb electrolyte, has stable electrochemical performance, overcomes the defects of non-woven fabric diaphragms in related technologies, and can fully meet the requirements of high-end products on lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery components, and more specifically, to a high-wettability aramid-coated diaphragm and a preparation method thereof. Background Art

[0002] Lithium-ion battery is a new type of battery with the advantages of high energy density, long cycle life, no memory effect, good stability, high reliability, environmental protection, fast charging, etc. It has been widely used in electronic equipment and small civilian appliances. In recent years, with the development of new energy vehicles, large energy storage equipment and other industries, lithium-ion batteries have become a new research hotspot, and these industries have put forward higher requirements on the performance of lithium batteries.

[0003] Lithium-ion battery separator is a thin film material with a microporous structure. It is an important component of lithium-ion batteries. It is usually used to isolate the positive and negative electrodes of lithium-ion batteries and prevent short circuits caused by direct contact between the positive and negative electrodes. The microporous structure of the separator can provide a transmission channel for the migration of lithium ions, which also makes the performance of the separator have a direct impact on the performance of the battery. Therefore, the separator is also called the "third electrode" in the battery. At present, the common lithium-ion battery separators on the market are mainly polyolefin separators and non-woven separators. Polyolefin separators have the advantages of low production cost, simple process, good mechanical strength and chemical stability, but poor thermal stability, while the thermal stability of non-woven separators is generally better than that of polyolefin separators.

[0004] Regarding the above-mentioned related technologies, the inventors believe that although non-woven fabric separators have certain advantages over polyolefin separators, they still have the defect of poor electrolyte wettability and are difficult to fully meet the requirements of high-end products for lithium batteries. Summary of the invention

[0005] In the related art, non-woven fabric separators have the defect of poor electrolyte wettability, which makes it difficult to fully meet the requirements of high-end products for lithium batteries. In order to improve this defect, the present application provides a high-wettability aramid coated separator and a preparation method thereof.

[0006] In a first aspect, the present application provides a highly wettable aramid coated diaphragm, which adopts the following technical solution: A highly wettable aramid coated diaphragm comprises a base membrane and a coating coated on the surface of the base membrane, wherein the base membrane is assembled from a non-woven fabric layer and a fibrillated fiber layer, the non-woven fabric layer contains lithium montmorillonite and EVOLi resin, the fibrillated fiber layer is composed of poly(p-phenylene benzobisoxazole) fibrillated fibers, and the coating is solidified from aramid slurry, which comprises the following components by weight percentage: 14-18% aromatic polyester, 3-5% adhesive, 0.8-1.2% nanoparticles, 3.5-5.5% diatomaceous earth, and the balance is supplemented to 100% by solvent.

[0007] By adopting the above technical solution, the present application assembles a non-woven fabric layer and a fibrillated fiber layer to obtain a base film with a composite structure, and uses aramid slurry to form a coating on the surface of the base film. The polyparaphenylene benzobisoxazole fibrillated fibers in the fibrillated fiber layer are composed of a series of microfibers of different diameters, and fibrillation makes these microfibers softer, so the contact between the microfibers is more sufficient. Through the overlap between microfibers of different diameters, a pore structure with higher complexity can be formed inside the fibrillated fiber layer, which can effectively overcome the defect of poor wettability of the non-woven fabric layer with the electrolyte after being composited with the non-woven fabric layer. The lithium-based montmorillonite and EVOLi resin in the non-woven fabric layer optimize the pore structure of the non-woven fabric layer, and introduce a large amount of hydroxyl groups, so that the compatibility between the non-woven fabric layer and the electrolyte is improved, which is beneficial to the base membrane to fully realize the infiltration and absorption of the electrolyte, and increase the contribution of the non-woven fabric layer to the wettability. During the curing process of the coating, the aromatic polyester forms a porous structure as the solvent evaporates, and the gaps formed by the accumulation of diatomaceous earth particles and nanoparticles and the microporous structure inside the diatomaceous earth particles make the pore structure formed by the aromatic polyester more complex. In addition, the silanol groups on the surface of the diatomaceous earth particles also have good compatibility with the electrolyte, so the coating can further improve the compatibility and wettability of the base film with the electrolyte. Under the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating, the high-wettability aramid coated diaphragm of the present application can fully wet and absorb the electrolyte, has stable electrochemical properties, good high-temperature dimensional stability and heat resistance, and has low thermal diffusion and a long cycle life, which overcomes the defects of the non-woven fabric diaphragm in the related art and can fully meet the requirements of high-end products for lithium-ion batteries.

[0008] Preferably, the nonwoven fabric layer is prepared according to the following method: (1) Lithium-modifying EVOH resin to obtain EVOLi resin, mixing the EVOLi resin with lithium-based montmorillonite, adding the mixture into solvent DMAc and stirring to obtain a spinning precursor solution; (2) The spinning precursor solution is sucked into the needle tube, and the spinning precursor solution is subjected to electrostatic spinning to obtain a non-woven fabric layer.

[0009] By adopting the above technical scheme, the present application first prepared EVOLi resin, lithium-based montmorillonite and DMAc to prepare a spinning precursor solution, and then used the spinning precursor solution to perform electrospinning to obtain a non-woven fabric layer containing EVOLi resin and lithium-based montmorillonite.

[0010] Preferably, the lithiation modification of the EVOH resin is carried out according to the following method: EVOH resin and lithium tert-butoxide are respectively added to the solvent DMAc to dissolve, and then 1,3-propane sultone is added to the DMAc solution of lithium tert-butoxide under heating conditions to obtain a modified liquid, and the modified liquid is added to the DMAc solution of EVOH resin. After continuing to stir, distilled water is added, the precipitated white substance is collected, and EVOLi resin is obtained after drying.

[0011] By adopting the above technical solution, the present application first uses lithium tert-butoxide and 1,3-propane sultone to react, so that 1,3-propane sultone undergoes ring opening, and obtains an intermediate product containing lithium alcoholate groups. Through the reaction of the intermediate product with EVOH resin, a part of the hydroxyl groups in the EVOH resin will be converted into lithium alcoholate groups, thereby obtaining EVOLi resin.

[0012] Preferably, the fibrillated fiber layer is assembled with the non-woven fabric layer in the following manner: The poly(p-phenylene benzobisoxazole) fibrillated fibers are added into a deflaking machine for deflaking to obtain a fiber slurry; a non-woven fabric layer is placed on a forming net of a paper sheet former, and the fiber slurry is added into the paper sheet former, and after stirring and dehydration, the poly(p-phenylene benzobisoxazole) fibrillated fibers in the fiber slurry are aggregated to form a fibrillated fiber layer, thereby completing the assembly of the fibrillated fiber layer and the non-woven fabric layer.

[0013] By adopting the above technical scheme, the present application firstly defibrillates the poly(p-phenylene benzobisoxazole) fibrillated fibers, and then uses a paper sheet former to transfer the poly(p-phenylene benzobisoxazole) fibrillated fibers to the surface of the non-woven fabric layer, completes the assembly of the fibrillated fiber layer and the non-woven fabric layer, and obtains a base film with a composite structure.

[0014] Preferably, in the method of assembling the fibrillated fiber layer and the non-woven fabric layer, a dispersant is further added to the fiber slurry, and the dispersant is polyoxyethylene ether.

[0015] By adopting the above technical scheme, polyoxyethylene ether can promote the uniform dispersion of poly(p-phenylene benzobisoxazole) fibrillated fibers, make the fiber distribution of the fibrillated fiber layer more uniform, and make the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating fully exerted, thereby improving the wettability of the diaphragm to the electrolyte.

[0016] Preferably, the amount of the polyoxyethylene ether is 0.8-1.2% of the weight of the poly(p-phenylene benzobisoxazole) fibrillated fiber.

[0017] By adopting the above technical solution, the present application optimizes the dosage of polyoxyethylene ether, which helps to improve the uniformity of the fibrillated fiber layer and improve the wettability of the diaphragm to the electrolyte.

[0018] Preferably, the diatomaceous earth in the aramid slurry is pretreated according to the following method before use: The diatomite is calcined in a muffle furnace, and after the diatomite is cooled, the diatomite is mixed with sodium silicate, and the mixture is wet-milled. After the ball milling is completed, the remaining slurry is filtered, and the filter cake is dried and then crushed to obtain purified diatomite.

[0019] By adopting the above technical solution, the present application removes organic matter in diatomite by calcination, and then removes soluble components by wet ball milling, thereby reducing impurities in the diatomite and obtaining diatomite with a more ideal pore structure.

[0020] Preferably, the nanoparticles include modified nano-silicon dioxide, and the modified nano-silicon dioxide is prepared according to the following method: Nano-silica and anhydrous toluene are mixed and stirred to obtain a silica dispersion, a silane coupling agent is added to the silica dispersion, and then the mixture is stirred under nitrogen protection and subjected to a temperature-raising reaction. The product is washed, filtered and dried to obtain modified nano-silica.

[0021] By adopting the above technical solution, the present application uses a silane coupling agent to modify nano-silica to obtain modified nano-silica. The organic chain segments on the surface of the modified nano-silica can hinder the agglomeration of nanoparticles, which is conducive to the formation of a pore structure, so that the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating can be fully exerted, thereby improving the wettability of the diaphragm to the electrolyte.

[0022] Preferably, in the method for preparing the modified nano-silica, the silane coupling agent is selected from one of KH550, KH560 and KH570.

[0023] By adopting the above technical scheme, the present application preferably selects the types of silane coupling agents used to modify nano-silica. These silane coupling agents can improve the dispersion effect while giving the modified nano-silica a certain polarity, which can improve the compatibility between the coating and the electrolyte, and help enhance the wettability of the diaphragm to the electrolyte.

[0024] In a second aspect, the present application provides a method for preparing a high-wettability aramid-coated diaphragm, using the following technical solution.

[0025] A method for preparing a highly wettable aramid coated diaphragm comprises the following steps: (1) mixing aromatic polyester, adhesive, nanoparticles, diatomaceous earth and solvent, stirring to obtain aramid slurry, and setting aside; performing corona pretreatment on the base film, and setting aside; (2) coating the aramid slurry on the surface of the base film to obtain a coating layer; (3) The coating layer is preheated and then dried with hot air to solidify the coating layer into a coating, thereby obtaining a highly wettable aramid coated diaphragm.

[0026] By adopting the above technical scheme, the present application first prepares the aramid slurry and performs corona pretreatment on the base film, so that the base film and the aramid slurry have a better bonding effect, and then the coating layer formed by the aramid slurry is cured into a coating on the surface of the base film to obtain a highly wettable aramid coated diaphragm.

[0027] In summary, this application has the following beneficial effects: 1. The present application assembles a non-woven fabric layer and a fibrillated fiber layer to obtain a base film with a composite structure, and uses aramid slurry to form a coating on the surface of the base film. Under the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating, the highly wettable aramid coated diaphragm of the present application can fully wet and absorb the electrolyte, has stable electrochemical properties, overcomes the defects of the non-woven fabric diaphragm in the related art, and can fully meet the requirements of high-end products for lithium-ion batteries.

[0028] 2. The present application selects polyoxyethylene ether as a dispersant, which can promote the uniform dispersion of poly(p-phenylene benzobisoxazole) fibrillated fibers, make the fiber distribution of the fibrillated fiber layer more uniform, and enable the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating to be fully exerted, thereby improving the wettability of the diaphragm to the electrolyte.

[0029] 3. The present application defines a method for pre-treating diatomite, wherein organic matter in the diatomite is removed by calcination, and then soluble components are removed by wet ball milling, thereby reducing impurities in the diatomite and obtaining diatomite with a more ideal pore structure. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0031] Preparation example of base film The following is an explanation using Preparation Example 1.

[0032] Preparation Example 1 In this preparation example, the base film is assembled from a non-woven fabric layer and a fibrillated fiber layer, and the non-woven fabric layer is prepared according to the following method: (1) 10 g of EVOH resin and 5.60 g of lithium tert-butoxide were added to two 100 mL portions of solvent DMAc for dissolution, and then 8.55 g of 1,3-propane sultone was added to the DMAc solution of lithium tert-butoxide under heating conditions at 60° C., and the modified solution was obtained after stirring and dissolving, and the modified solution was added to the DMAc solution of EVOH resin, and the mixture was stirred and stirred for 3 hours, and then distilled water was added, and the precipitated white substance was collected and dried to obtain EVOLi resin; 4.85 g of EVOLi resin was mixed with 0.15 g of lithium montmorillonite, and the mixture was added to 20 g of solvent DMAc for stirring to obtain a spinning precursor solution; (2) The spinning precursor solution was sucked into the needle tube, and the spinning precursor solution was electrospun under the conditions of 18.00 kV, a propulsion speed of 0.3 mL / h, and a spinning roller speed of 200 r / min to obtain a non-woven fabric layer with an average thickness of 20 μm.

[0033] The fibrillated fiber layer and the nonwoven fabric layer are assembled as follows: The poly(p-phenylene benzobisoxazole) fibrillated fibers are added to a deflaking machine and deflaked for 30,000 revolutions to obtain a fiber slurry; a non-woven fabric layer is placed on a forming net of a paper sheet former, and the fiber slurry is added to the paper sheet former. After stirring and dehydration, the poly(p-phenylene benzobisoxazole) fibrillated fibers in the fiber slurry are aggregated to form a 15 μm thick fibrillated fiber layer, thereby completing the assembly of the fibrillated fiber layer and the non-woven fabric layer to obtain a base film.

[0034] Preparation Example 2 The difference between this preparation example and preparation example 1 is that, in the method of assembling the fibrillated fiber layer and the non-woven fabric layer, a dispersant is also added to the fiber slurry before adding the fiber slurry to the paper sheet former. The dispersant is polyoxyethylene ether with an average molecular weight of 5000000, and the amount of polyoxyethylene ether used is 0.5% of the weight of the poly(p-phenylene benzobisoxazole) fibrillated fiber.

[0035] Preparation Example 3 The difference between this preparation example and preparation example 2 is that the amount of polyoxyethylene ether used is 0.8% of the weight of the poly(p-phenylene benzobisoxazole) fibrillated fiber.

[0036] Preparation Example 4 The difference between this preparation example and preparation example 2 is that the amount of polyoxyethylene ether used is 1.0% by weight of the poly(p-phenylene benzobisoxazole) fibrillated fiber.

[0037] Preparation Example 5 The difference between this preparation example and preparation example 2 is that the amount of polyoxyethylene ether used is 1.2% of the weight of the poly(p-phenylene benzobisoxazole) fibrillated fiber.

[0038] Preparation example of modified nano-silica The following is an explanation using Preparation Example 6.

[0039] Preparation Example 6 In this preparation example, methyltrimethoxysilane is used as the silane coupling agent.

[0040] In this preparation example, modified nano-silica was prepared according to the following method: 15 g of nano-silica and 200 mL of anhydrous toluene were mixed and stirred to obtain a silica dispersion. 15 g of silane coupling agent was added to the silica dispersion, and then the mixture was stirred for 1 h under nitrogen protection. The mixture was heated to 125° C. and reacted for 4 h. The product was washed, filtered and dried to obtain modified nano-silica.

[0041] Preparation Example 7 The difference between this preparation example and preparation example 6 is that KH550 is used as the silane coupling agent.

[0042] Preparation Example 8 The difference between this preparation example and preparation example 6 is that KH560 is used as the silane coupling agent.

[0043] Preparation Example 9 The difference between this preparation example and preparation example 6 is that KH570 is used as the silane coupling agent.

[0044] Preparation Example of Aromatic Polyester The following is an explanation using Preparation Example 10 as an example.

[0045] Preparation Example 10 In this preparation example, the aromatic polyester was prepared according to the following method: (1) 1 mol of (3,5-dimethoxyphenyl)oxy-isophthalic acid and 1.5 mol of hydroquinone are mixed, 0.1 mol of tetrabutyl titanate is added as a catalyst, and the mixture is heated and polymerized at 195° C. under normal pressure for 12 hours to obtain a prepolymer; (2) The prepolymer was heated at 225° C. and 0.05 MPa for 16 h to obtain an aromatic polyester. Example

[0046] Examples 1-5 The following description is given by taking Example 1 as an example.

[0047] Example 1 This embodiment provides a highly wettable aramid coated diaphragm, comprising a base film and a coating coated on the surface of the base film, wherein the base film is prepared according to the method of Preparation Example 1, and the coating is formed by curing aramid slurry. The aramid slurry comprises the following components by weight percentage: 14% aromatic polyester, 3% adhesive, 0.8% nanoparticles, 3.5% diatomaceous earth, and the remainder is supplemented to 100% by solvent. The aromatic polyester is prepared according to the method of Preparation Example 10, the adhesive is a vinylidene fluoride-trifluoroethylene copolymer, the nanoparticles are nano-silicon dioxide, and the solvent is DMF.

[0048] This embodiment provides a method for preparing a high-wettability aramid coated diaphragm, comprising the following steps: (1) mixing aromatic polyester, adhesive, nanoparticles, diatomaceous earth and solvent, stirring to obtain aramid slurry, and setting aside; performing corona pretreatment on the base film, and setting aside; (2) The aramid slurry is coated on both sides of the base film by gravure coating at a coating rate of 5 m / min to obtain a coating layer; (3) The coating layer is preheated with water vapor for 15 s in an environment with 95% humidity, and then hot air dried to solidify the coating layer into a 5 μm thick coating to obtain a highly wettable aramid coated diaphragm.

[0049] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the aramid slurry.

[0050] Table 1 Ratio of raw materials for aramid slurry Example 6 The difference between this embodiment and embodiment 5 is that the base film is prepared according to the method of preparation example 2.

[0051] Example 7 The difference between this embodiment and embodiment 5 is that the base film is prepared according to the method of preparation example 3.

[0052] Example 8 The difference between this embodiment and Embodiment 5 is that the base film is prepared according to the method of Preparation Example 4.

[0053] Example 9 The difference between this embodiment and Embodiment 5 is that the base film is prepared according to the method of Preparation Example 5.

[0054] Example 10 The difference between this embodiment and embodiment 9 is that the diatomaceous earth in the aramid slurry is pretreated according to the following method before use: The diatomite was calcined at 400°C for 1.5 h in a muffle furnace. After the diatomite was cooled, the diatomite was mixed with sodium silicate in a weight ratio of 97:3. The mixture was wet-milled in a ball mill equipped with zirconium oxide grinding balls. After 20 min, the remaining slurry was filtered, and the filter cake was dried and then crushed to obtain purified diatomite.

[0055] Embodiment 11 The difference between this embodiment and embodiment 10 is that the nanoparticles are formed by mixing nano-silicon dioxide and the modified nano-silicon dioxide of preparation example 6 in a weight ratio of 1:1.

[0056] Example 12 The difference between this embodiment and embodiment 11 is that the modified nano-silica is prepared according to the method of preparation example 7.

[0057] Example 13 The difference between this embodiment and embodiment 11 is that the modified nano-silica is prepared according to the method of preparation example 8.

[0058] Embodiment 14 The difference between this embodiment and embodiment 11 is that the modified nano-silica is prepared according to the method of preparation example 9.

[0059] -Comparative ratio Comparative Example 1 The difference between this comparative example and Example 1 is that a PET non-woven fabric with a thickness of 35 μm and a porosity of 62% is selected as the base film, and the components of the aramid slurry do not include nanoparticles and diatomaceous earth.

[0060] Comparative Example 2 The difference between this comparative example and Example 1 is that a PET non-woven fabric with a thickness of 35 μm and a porosity of 62% is selected as the base film.

[0061] Comparative Example 3 The difference between this comparative example and Example 1 is that the components of the aramid slurry do not include nanoparticles.

[0062] Comparative Example 4 The difference between this comparative example and Example 1 is that the components of the aramid slurry do not include diatomaceous earth.

[0063] Performance testing methods The liquid absorption rate of the diaphragm was detected using electrolyte, and the electrolyte parameters were: 1 mol / LLiPF6 / EC∶DMC∶EMC (volume ratio 1∶1∶1) / 1%VC.

[0064] In a glove box, a circular diaphragm with a diameter of 16 mm was immersed in an electrolyte, and after immersion for 30 minutes, it was taken out and weighed, and the calculation method was the weight increased after immersion / weight of the dry film before immersion × 100%. After the test and calculation were completed, the liquid absorption rate of Comparative Example 1 was used as a reference to calculate the ratio between the liquid absorption rate of each embodiment and the comparative example and the liquid absorption rate of Comparative Example 1, and the ratio was recorded as the relative liquid absorption rate. The results are shown in Table 2.

[0065] Table 2 Relative liquid absorption rate It can be seen from Examples 1-5 and Comparative Example 1 and Table 2 that the relative liquid absorption rates measured in Examples 1-5 are all higher than those in Comparative Example 1. This is because under the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating, the high wettability aramid coated diaphragm of Examples 1-5 can fully wet and absorb the electrolyte and have stable electrochemical properties, thus overcoming the defects of the non-woven fabric diaphragm in the related art and being able to fully meet the requirements of high-end products for lithium-ion batteries.

[0066] Combining Example 1 and Comparative Example 2 and Table 2, it can be seen that the relative liquid absorption rate measured in Example 1 is higher than that in Comparative Example 2. This is because the base film of Comparative Example 2 lacks lithium-based montmorillonite and EVOLi resin, and therefore fails to fully overcome the defects of the non-woven fabric itself. Even if the coating contains nanoparticles and diatomaceous earth, it fails to fully improve the wettability of the diaphragm to the electrolyte.

[0067] Combining Example 1 and Comparative Examples 3-4 and Table 2, it can be seen that the relative liquid absorption rate measured in Example 1 is higher than that in Comparative Examples 3-4. This is because the aramid slurry of Comparative Example 3 lacks diatomaceous earth or nanoparticles, and it is difficult to produce sufficient gaps through the accumulation of particles, so the wettability of the diaphragm to the electrolyte is not fully improved.

[0068] Combining Example 5 and Example 6 and Table 2, it can be seen that the relative liquid absorption rate measured in Example 6 is higher than that in Example 5. This is because polyoxyethylene ether can promote the uniform dispersion of poly(p-phenylene benzobisoxazole) fibrillated fibers, making the fiber distribution of the fibrillated fiber layer more uniform, so that the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating can be fully exerted, thereby improving the wettability of the diaphragm to the electrolyte.

[0069] Combining Examples 6-9 and Table 2, it can be seen that when the amount of polyoxyethylene ether is 0.8-1.2% of the weight of the poly(p-phenylene benzobisoxazole) fibrillated fibers, the poly(p-phenylene benzobisoxazole) fibrillated fibers are more evenly dispersed, which helps to fully improve the wettability of the separator to the electrolyte.

[0070] Combining Example 9, Example 10 and Table 2, it can be seen that the relative liquid absorption rate measured in Example 10 is higher than that in Example 9. This is because the pretreatment removes impurities in the diatomaceous earth and obtains diatomaceous earth with a more ideal pore structure, so the diaphragm can better infiltrate and adsorb the electrolyte.

[0071] It can be seen from Example 10, Example 11 and Table 2 that the relative liquid absorption rate measured in Example 11 is higher than that in Example 10. This is because the organic chain segments on the surface of the modified nano-silica can hinder the agglomeration of the nanoparticles, which is beneficial to the formation of the pore structure, so that the synergistic effect of the non-woven fabric layer, the fibrillated fiber layer and the coating can be fully exerted, thereby improving the wettability of the diaphragm to the electrolyte.

[0072] It can be seen from Example 11, Examples 12-14 and Table 2 that the relative liquid absorption rate measured in Examples 12-14 is higher than that in Example 11. This is because the silane coupling agents KH550, KH560 and KH570 can impart a certain polarity to the modified nano-silica, improve the compatibility between the coating and the electrolyte, and help enhance the wettability of the diaphragm to the electrolyte.

[0073] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A highly wettable aramid coated diaphragm, characterized in that: The invention comprises a base film and a coating coated on the surface of the base film, wherein the base film is assembled from a non-woven fabric layer and a fibrillated fiber layer, the non-woven fabric layer contains lithium montmorillonite and EVOLi resin, the fibrillated fiber layer is composed of poly(p-phenylene benzobisoxazole) fibrillated fibers, and the coating is solidified from aramid slurry, which comprises the following components by weight percentage: 14-18% aromatic polyester, 3-5% adhesive, 0.8-1.2% nanoparticles, 3.5-5.5% diatomaceous earth, and the balance is supplemented to 100% by solvent.

2. The high wettability aramid coated diaphragm according to claim 1, characterized in that: The nonwoven fabric layer is prepared as follows: (1) Lithium-modifying EVOH resin to obtain EVOLi resin, mixing the EVOLi resin with lithium-based montmorillonite, adding the mixture into solvent DMAc and stirring to obtain a spinning precursor solution; (2) The spinning precursor liquid is sucked into the needle tube, and the spinning precursor liquid is subjected to electrostatic spinning to obtain a non-woven fabric layer.

3. The high wettability aramid coated diaphragm according to claim 2, characterized in that: The lithiation modification of the EVOH resin is carried out according to the following method: EVOH resin and lithium tert-butoxide are respectively added to the solvent DMAc to dissolve, and then 1,3-propane sultone is added to the DMAc solution of lithium tert-butoxide under heating conditions to obtain a modified liquid, and the modified liquid is added to the DMAc solution of EVOH resin. After continuing to stir, distilled water is added, the precipitated white substance is collected, and EVOLi resin is obtained after drying.

4. The high wettability aramid coated diaphragm according to claim 2, characterized in that: The fibrillated fiber layer is assembled with the nonwoven fabric layer in the following manner: The poly(p-phenylene benzobisoxazole) fibrillated fibers are added into a deflaking machine for deflaking to obtain a fiber slurry; a non-woven fabric layer is placed on a forming net of a paper sheet former, and the fiber slurry is added into the paper sheet former, and after stirring and dehydration, the poly(p-phenylene benzobisoxazole) fibrillated fibers in the fiber slurry are aggregated to form a fibrillated fiber layer, thereby completing the assembly of the fibrillated fiber layer and the non-woven fabric layer.

5. The high wettability aramid coated diaphragm according to claim 4, characterized in that: In the method for assembling the fibrillated fiber layer and the non-woven fabric layer, a dispersant is also added to the fiber slurry, and the dispersant is polyoxyethylene ether.

6. The high wettability aramid coated diaphragm according to claim 5, characterized in that: The amount of the polyoxyethylene ether used is 0.8-1.2% of the weight of the poly(p-phenylene benzobisoxazole) fibrillated fiber.

7. The high wettability aramid coated diaphragm according to claim 1, characterized in that: The diatomaceous earth in the aramid slurry is pretreated according to the following method before use: The diatomite is calcined in a muffle furnace, and after the diatomite is cooled, the diatomite is mixed with sodium silicate, and the mixture is wet-milled. After the ball milling is completed, the remaining slurry is filtered, and the filter cake is dried and then crushed to obtain purified diatomite.

8. The high wettability aramid coated diaphragm according to claim 7, characterized in that: The nanoparticles include modified nano-silicon dioxide, and the modified nano-silicon dioxide is prepared according to the following method: Nano-silica and anhydrous toluene are mixed and stirred to obtain a silica dispersion, a silane coupling agent is added to the silica dispersion, and then the mixture is stirred under nitrogen protection and subjected to a temperature-raising reaction. The product is washed, filtered and dried to obtain modified nano-silica.

9. The high wettability aramid coated diaphragm according to claim 8, characterized in that: In the method for preparing the modified nano-silica, the silane coupling agent is selected from one of KH550, KH560 and KH570.

10. The method for preparing a highly wettable aramid coated diaphragm according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing aromatic polyester, adhesive, nanoparticles, diatomaceous earth and solvent, stirring to obtain aramid slurry, and setting aside; performing corona pretreatment on the base film, and setting aside; (2) coating the aramid slurry on the surface of the base film to obtain a coating layer; (3) The coating layer is preheated and then dried with hot air to solidify the coating layer into a coating, thereby obtaining a highly wettable aramid coated diaphragm.

Citation Information

Patent Citations

  • Thermal insulation fireproof composite material and preparation method thereof

    CN103306157A

  • Lithium ion battery diaphragm, preparation method of lithium ion battery diaphragm and lithium ion battery

    CN104157812A

  • Aramid fiber polymer coated lithium ion battery membrane and preparation method thereof

    CN104979515A

  • Non-woven fabric ceramic diaphragm for lithium ion battery and preparation method of non-woven fabric ceramic diaphragm

    CN105185937A

  • Heat-resistant liquid-absorbing diaphragm for lithium ion battery and preparation method

    CN111192998A